Determination of vitamin B12 absorption by a simple whole body counter. Issue 5 (September 1968) - Finlayson, N. D. C.; Shearman, D. J. C.; Simpson, J. D.; Girdwood, R. H.
Abstract : This paper reports the results of estimating vitamin B12 absorption by whole body counting in patients without known gastrointestinal disorder, and in patients with pernicious anaemia, idiopathic achlorhydria, achlorhydria following gastric operations, and various forms of small intestinal disease. Patients with pernicious anaemia absorbed less than 30% of the test dose; they could be distinguished from patients without gastrointestinal abnormality and from most achlorhydric patients who secreted more than 300 mg units of intrinsic factor in the post-histamine hour. Nevertheless, the wide range of normal absorption and the variable absorption from the normal gastrointestinal tract is emphasized and discussed. There is no relation between histamine-stimulated intrinsic factor production and vitamin B12 absorption in patients with small intestinal disease.